Characteristics of community savings groups in rural Eastern Uganda: opportunities for improving access to maternal health services. (1st August 2017) - Mutebi, Aloysius; Muhumuza Kananura, Rornald; Ekirapa-Kiracho, Elizabeth; Bua, John; Namusoke Kiwanuka, Suzanne; Nammazi, Gertrude; Paina, Ligia; Tetui, Moses
ABSTRACT: Background : Rural populations in Uganda have limited access to formal financial Institutions, but a growing majority belong to saving groups. These saving groups could have the potential to improve household income and access to health services. Objective: To understand organizational characteristics, benefits and challenges, of savings groups in rural Uganda. Methods : This was a cross-sectional descriptive study that employed both quantitative and qualitative data collection techniques. Data on the characteristics of community-based savings groups (CBSGs) were collected from 247 CBSG leaders in the districts of Kamuli, Kibukuand Pallisa using self-administered open-ended questionnaires. To triangulate the findings, we conducted in-depth interviews with seven CBSG leaders. Descriptive quantitative and content analysis for qualitative data was undertaken respectively. Results : Almost a quarter of the savings groups had 5–14 members and slightly more than half of the saving groups had 15–30 members. Ninety-three percent of the CBSGs indicated electing their management committees democratically to select the group leaders and held meetings at least once a week. Eighty-nine percent of the CBSGs had used metallic boxes to keep their money, while 10% of the CBSGs kept their money using mobile money and banks, respectively. The main reasons for the formation of CBSGs were to increase household income, developing the community and saving for emergencies. The most common challenges associated with CBSG management included high illiteracy (35%) among the leaders, irregular attendance of meetings (22%), and lack of training on management and leadership(19%). The qualitative findings agreed with the quantitative findings and served to triangulate the main results. Conclusions : Saving groups in Uganda have the basic required structures; however, challenges exist in relation to training and management of the groups and their assets. The government and development partners should work together to provide technical support to the groups.